History of the Early Establishment of the Abbasiyah Dynasty - Firma Hafmi; Fatmawati; Muhammad Hanafi (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
This research aims to explore in-depth the formation process of the Abbasid Dynasty in the history of Islamic civilization. This qualitative study employs a historical approach to understand two key methods in this process. Data collection techniques involve literature reviews and historical document analysis, while data analysis is conducted through content analysis. Data validation is carried out by cross-referencing various historical sources to ensure the accuracy of the information. The research findings indicate that the Abbasid Dynasty used propaganda through secret networks to gain public support and garner sympathy from various segments of society, as well as to build military strength to challenge and overthrow the Umayyad power. This study reveals the crucial role of political communication and military strategy in the formation and stability of the government, as well as its impact on the political and social dynamics of the society at that time. Thus, this research provides a comprehensive insight into the formation process of the Abbasid Dynasty and its impact on Islamic civilization.